2023
DOI: 10.1038/s41598-023-35958-z
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid-treated bed nets impair blood feeding performance in insecticide resistant mosquitoes

Abstract: The blood feeding performance of female mosquitoes directly impacts their ability to transmit malaria. Yet their host seeking and blood feeding behaviours in the presence of insecticide-treated nets (ITNs) are still poorly understood. This work explores how both insecticide resistant and susceptible Anopheles gambiae s.l. mosquitoes interact with pyrethroid nets (PermaNet 2.0 or Olyset net) or an untreated net (UTN) while attempting to blood feed on a human arm. Regardless of mosquito resistance status, the IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Finally. as observed by other studies [44][45][46][47][48][49] pyrethroid-only nets still provided some protection in this area of pyrethroid resistance. Non-users of nets in clusters where chlorfenapyr-pyrethroid nets were used were better protected than non-users in clusters where pyrethroid only nets were used, but even the more effective nets did not adequately control malaria and infection prevalence was still very high even amongst users of these nets.…”
Section: Discussionsupporting
confidence: 78%
“…Finally. as observed by other studies [44][45][46][47][48][49] pyrethroid-only nets still provided some protection in this area of pyrethroid resistance. Non-users of nets in clusters where chlorfenapyr-pyrethroid nets were used were better protected than non-users in clusters where pyrethroid only nets were used, but even the more effective nets did not adequately control malaria and infection prevalence was still very high even amongst users of these nets.…”
Section: Discussionsupporting
confidence: 78%
“…Fatou and Müller [24] found that while permethrin-treated nets had no detectable repellent effect on mosquitoes, they elicited a strong irritant response resulting in contact disengagement, allowing both susceptible and resistant forms to pass more easily through holes in treated nets than untreated nets. Barreaux et al [25] recently reported that although the duration of bloodfeeding was significantly reduced when feeding through an ITN, A. gambiae s.l. could compensate by increasing its ingested blood flow rate by 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Barreaux et al . [ 25 ] recently reported that although the duration of bloodfeeding was significantly reduced when feeding through an ITN, A. gambiae s.l. could compensate by increasing its ingested blood flow rate by 35%.…”
Section: Discussionmentioning
confidence: 99%
“…The latter could trigger an avoidance behaviour in the vectors [ 48 ], affecting their ability to take a blood meal. As a key parameter influencing malaria transmission potential [ 49 ], blood-feeding behaviour observed with new nets could benefit malaria vector control interventions [ 42 44 ]. This result confirms that high-dose pyrethroids would continue to play a valuable role in blood-feeding inhibition and personal protection [ 50 ].…”
Section: Discussionmentioning
confidence: 99%